2007
DOI: 10.1111/j.1439-037x.2007.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Temperature on Key Enzymes Involved in Starch and Protein Formation in Grains of Two Wheat Cultivars

Abstract: High temperature is a major determinant of grain growth and yield formation in wheat. The present study was undertaken to investigate the effects of high temperature regimes on the activities of key regulatory enzymes involved in starch and protein accumulation in grains of two winter wheat (Triticum aestivum L.) cultivars Yangmai 9 and Xuzhou 26 with different protein contents. Four day/night temperature regimes of 34 °C/22 °C, 32 °C/24 °C, 26 °C/14 °C and 24 °C/16 °C were established after anthesis, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 24 publications
7
74
2
Order By: Relevance
“…However, at that stage of kernel maturation the environmental temperatures start to increase, affecting the enzyme activity as well as gene expression (Hurkman et al, 2003). Therefore, it is supposed that GBSS I might have been less active or in lower amounts possibly due to the sensitivity of substituted triticales to high temperatures at which they were grown (Liu et al, 2011;Zhao, Dai, Jiang, & Cao, 2008) in comparison to complete triticales. However, we were unable to demonstrate that because the kernels of the triticale genotypes were analyzed in a mature state and no information about the environmental growing conditions under which they were grown was available.…”
Section: Results and Discussion Total Carbohydrate Starch And Amylosmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at that stage of kernel maturation the environmental temperatures start to increase, affecting the enzyme activity as well as gene expression (Hurkman et al, 2003). Therefore, it is supposed that GBSS I might have been less active or in lower amounts possibly due to the sensitivity of substituted triticales to high temperatures at which they were grown (Liu et al, 2011;Zhao, Dai, Jiang, & Cao, 2008) in comparison to complete triticales. However, we were unable to demonstrate that because the kernels of the triticale genotypes were analyzed in a mature state and no information about the environmental growing conditions under which they were grown was available.…”
Section: Results and Discussion Total Carbohydrate Starch And Amylosmentioning
confidence: 99%
“…Therefore, considering that the B-granules enlarge towards the end of the grain-filling period when high temperatures prevail, their synthesis might have been more affected in the substituted triticales than in the complete ones. High environmental temperatures from anthesis to maturity reduce the duration of starch accumulation, inducing significant changes in starch granule size distribution of grains in wheat (Chi, Seib, & Bernardin, 1994;Hurkman et al, 2003;Zhao et al, 2008), leading to a significant reduction in amylopectin and starch contents with no amylose content alteration (Lu et al, a Volume ( Nota: Los valores promedio están expresados en porcentaje ± desviación estándar. Valores seguidos por la misma letra en la misma columna no son significativamente diferentes (P ≤ 0,05, n = 3).…”
Section: Starch Granule Size Distributionmentioning
confidence: 99%
“…9). Various authors [58][59][60] reported that high temperature after flowering reduced the starch content and significantly influenced starch granule size distribution in wheat kernels. …”
Section: Protein and Starch Contentmentioning
confidence: 99%
“…During grain-filling unfavorable climatic conditions can led to alterations in protein deposition and starch biosynthesis, and thus starch characteristics (Balla et al, 2011). Exposure to high temperatures may severely influence starch accumulation in cereal endosperm due to susceptibility of starch enzymes (Barnabas et al, 2008;Zhao et al, 2008). It is reported that even short period of elevated temperatures (35-40°C) during grain growth have influence on quality of the grain (Viswanathan and Khanna-Chopra, 2001).…”
Section: Introductionmentioning
confidence: 99%